2013
DOI: 10.4084/mjhid.2013.042
|View full text |Cite
|
Sign up to set email alerts
|

Acute Panmyelosis with Myelofibrosis - A Rare Subtype of Acute Myeloid Leukemia

Abstract: One case of acute panmyelosis with myelofibrosis (APMF) is here reported. A 45 year old male presented with abrupt onset of rapidly progressing low backache, weakness and pancytopenia. On examination there was no organomegaly. Peripheral blood examination revealed normocytic normochromic red blood cells with 10% circulating blasts. Flowcytometric examination of peripheral blood revealed blasts which were positive for CD34, HLA− DR and myeloid associated antigens (i.e. CD13 and CD33). Blasts were negative for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Although MF patients are not typically CD33 positive, acute panmyelosis with MF, a specific subtype of MF, has been found to display this cellular marker. 59 Additionally, other studies on MF patients have found that spleens of MF patients can contain populations of CD33 malignant hematopoietic stem cells. 60 This suggests that, for those who are not candidates for intensive therapy or who do not have alternative treatment options and are CD33 positive, gemtuzumab should be considered.…”
Section: Initial Blast-phase Treatment Optionsmentioning
confidence: 99%
“…Although MF patients are not typically CD33 positive, acute panmyelosis with MF, a specific subtype of MF, has been found to display this cellular marker. 59 Additionally, other studies on MF patients have found that spleens of MF patients can contain populations of CD33 malignant hematopoietic stem cells. 60 This suggests that, for those who are not candidates for intensive therapy or who do not have alternative treatment options and are CD33 positive, gemtuzumab should be considered.…”
Section: Initial Blast-phase Treatment Optionsmentioning
confidence: 99%
“…APMF usually presents with pancytopenia in the peripheral blood with absent or only rare circulating blasts without overt anisopoikilocytosis [ 20 ]. Splenomegaly is absent, and extramedullary hematopoiesis in the spleen is not prominent [ 21 ]. The clinical course of APMF is rapidly progressive and fatal often terminating with an overt acute leukemia, therefore, it is essential to make the accurate diagnosis and distinguish it from its mimickers, particularly acute megakaryoblastic leukemia (AML-M7) through a detailed clinical history and hematological work up [ 20 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Follow-up revealed that immunohistochemistry was not contributing towards a definite diagnosis and the patient was treated as a case of acute myeloid leukaemia and there was improvement in symptoms. Many published articles consider APMF as a variant of myelodysplastic syndrome [ 13 ]. It is important to have knowledge about this entity since these patients need aggressive management due to the rapidly fatal course and poor outcome associated with this condition.…”
Section: Discussionmentioning
confidence: 99%